2011
DOI: 10.1002/pssb.201147350
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐state structure of KNbO3/KTaO3 superlattices: Array of nearly independent ferroelectrically ordered planes

Abstract: Phonon spectra of the paraelectric phase, structure and distribution of polarization in the polar ground state, and energies of ferroelectrically and antiferroelectrically ordered phases were calculated for stress-free (KNbO3)1(KTaO3)n superlattices (n = 1-7) from first principles within the densityfunctional theory. Quasi-two-dimensional ferroelectric state with the polarization localized in the KNbO3 layer was revealed to be the ground state for the superlattices with n ≥ 2. The interaction between these pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(78 reference statements)
3
3
0
Order By: Relevance
“…It can be seen that in addition to the instability at the Γ point, the instabilities also appear at the X, R, and Z points of the Brillouin zone. We have already encountered a similar situation in KNbO 3 /KTaO 3 [7] and BaTiO 3 /BaZrO 3 [9] SLs.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…It can be seen that in addition to the instability at the Γ point, the instabilities also appear at the X, R, and Z points of the Brillouin zone. We have already encountered a similar situation in KNbO 3 /KTaO 3 [7] and BaTiO 3 /BaZrO 3 [9] SLs.…”
Section: Resultssupporting
confidence: 54%
“…Most of the previous studies of ferroelectric perovskite superlattices were carried out on II-IV/II-IV or I-V/I-V type superlattices (here, the numbers indicate the valence of atoms that enter the A and B sites of the AB O 3 perovskite structure). In such SLs, there are no double electric layers at the interface between two dielectric materials, and therefore, they are macroscopically electrically neutral both in the bulk and at the interface (see [1][2][3][4][5][6][7][8][9][10] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that in addition to the instability at the Γ point, the instabilities also appear at the X, R, and Z points of the Brillouin zone. We have already encountered a similar situation in KNbO 3 /KTaO 3 [42] and BaTiO 3 /BaZrO 3 [44] SLs. xy-polarized displacements of Bi and oxygen atoms lying in the same xy plane are stronger; this displacement pattern is characteristic of BiScO 3 .…”
Section: Search For the Ground-state Structuresupporting
confidence: 54%
“…A similar instability region along the path Γ-Z-R-X-Γ was observed in KNbO 3 /KTaO 3 superlattices. 5 Among the possible polar phases resulting from the condensation of the unstable E u mode at the Γ point, the Amm2 phase with polarization along the [110] direction has the lowest energy in (BaTiO 3 ) 1 (BaZrO 3 ) n SLs with n = 1-7. However, the phonon spectra of this phase ( Fig.…”
Section: B the Batio3/bazro3 Superlatticesmentioning
confidence: 99%
“…The recent studies of the ferroelectric instability in free-standing (KNbO 3 ) 1 (KTaO 3 ) n superlattices grown in the [001] direction showed that, with increasing n, the tendency to the ferroelectric ordering is retained in KNbO 3 layers with a thickness of one unit cell while the interaction energy between neighboring KNbO 3 layers exponentially decreases. 4,5 It was shown that at n ≥ 2 the ground state of the SLs is an array of ferroelectrically polarized planes whose polarization is concentrated in the KNbO 3 layer, is parallel to the [110] direction, and weakly interacts with polarization in neighboring layers. The use of such arrays of quasi-two-dimensional ferroelectric planes as a medium for the three-dimensional data recording can make it possible to achieve a volume recording density of ∼10 18 bit/cm 3 .…”
Section: Introductionmentioning
confidence: 99%